Caracterización del potencial biológico de Bacillus SPP. Y sus metabolitos para el control de colletotrichum acutatum causante de la antracnosis del chocho andino (Lupinus Mutabilis) en las provincias del Chimborazo y Cotopaxi - Oliva Torres, Carlos Eduardo (2015)
The Andean lupin or tarwi (Lupinus mutabilis) is a traditional crop of the Ecuadorian region and other countries such as Peru and Bolivia. Due to its high nutritional value is an important domestic agrofood resource, especially for native population. One of the main phytosanitary issues of lupine crops are plant fungal diseases. In Ecuador, anthracnose caused by Colletotrichum acutatum is the most destructive fungal disease of Andean lupin. Currently, the control of this pathogen is done using chemical fungicides, which increase the cost of production and represent an increase in product toxicity. Other strategies used by farmers are to plant seeds agronomically improved varieties by INIAP and selection of own seed after harvest seed. However, this activity increases the risk of impact and spread of anthracnose due to use of contaminated and low quality materials. Because of this, use of alternative methods such as biological control are important, thanks to the lower toxicity of the biological products compared to the chemical fungicides, and the fact that they are biodegradable in short periods of time. In biological control, the use of microorganisms such as bacteria of Bacillus spp. genus and their metabolites have been successful in reducing pre and post-harvest fungal diseases including legumes. For this reason it is important to evaluate the antifungal activity of native bacteria within the management and control of C. acutatum caused anthracnose. At present research, the effectiveness of native isolates from Salcedo and Zumbahua were evaluated in both in vitro and in vivo assays against C. acutatum, using fresh cells and its metabolites. Two strains of Bacillus subtilis showed high antagonistic potential against C. acutatum and high antifungal activity in all tests were obtained.